Features Of Symbolic Interpretation - Nasirov Azimidin Normamatovich (Research Parks Publishing LLC, 2021)
When we talk about the form of expression of artistic and poetic changes in the development of the Uzbek novel, we see that the evolution of human thought is artistically interpreted on the basis of symbolism and metaphors. Isajon Sultan's novel Bogiy Darbadar (Eternal Wanderer) is a philosophical interpretation of the suffering underlying human tragedy, the path to self-realization. The article is devoted to the interpretation in the novel of contradictions, symbols and metaphors used to express the inner world of a person